CURRENCY DEVALUATION, STOCK MARKET RETURNS AND ECONOMIC GROWTH IN SUB SAHARAN AFRICA COUNTRIES - OLABISI, OLABODE ERIC; VICTOR, SADIBO OLANREWAJU (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
Achieving sustainable growth in the world economies is one of the United Nations Sustainable Development Goals and also one of the macroeconomic goals targeting Sub-Saharan Africa. As the region aimed to attain growth and development, policy toward currency devaluation and stock market returns became crucial. Hence, this study examined the relationship between currency devaluation, stock market returns and economic growth in Sub-Saharan African (SSA) countries from 2003 to 2023 within the framework of the Mundell-Fleming model. Using panel error components general least squares (PEGLS) and the Dumitrescu-Hurlin panel Granger causality test econometric techniques, findings indicated that currency devaluation and stock market returns are positive and statistically significant to promote the economies of SSA countries. Findings further showed that there is unidirectional causality between balance of payment and currency devaluation, running from balance of payment and not vice versa. The research recommends policies that gear towards improved stock market performances. Also, there is a need for strategic policy that promotes currency devaluation in the SSA region.